Prediction of SDG 6.2 Achievement in Indonesia Using Double Exponential Smoothing - Nabila, Nazwa; Erfina, Adhitia; Warman, Cecep (ISB Atma Luhur, 2025)
This research aims to forecast Indonesia’s progress in achieving Sustainable Development Goal (SDG) 6.2, which targets 100% access to adequate sanitation and elimination of open defecation (OD) by 2030. The Double Exponential Smoothing (DES) method was used on provincial time series data from 2013–2024 (sanitation) and 2020–2024 (OD), with performance evaluated using Mean Absolute Percentage Error (MAPE). Results showed consistently high forecasting accuracy, with DKI Jakarta (0.99%), South Sulawesi (1.87%), and DI Yogyakarta (2.21%) among the most accurate for sanitation, and Maluku (2.79%), Papua (3.03%), and Gorontalo (4.49%) for OD. Spearman correlation analysis revealed a strong national negative correlation (r = –0.991, p < 0.001) between sanitation access and OD. However, provinces like DKI Jakarta (+0.36) and DI Yogyakarta (+0.86) showed positive anomalies, indicating behavioral gaps despite infrastructure growth. These findings clearly highlight the importance of integrating behavioral interventions and localized strategies to effectively accelerate progress toward SDG 6.2.